3y+12=-3x

Simple and best practice solution for 3y+12=-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y+12=-3x equation:


Simplifying
3y + 12 = -3x

Reorder the terms:
12 + 3y = -3x

Solving
12 + 3y = -3x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + 3y = -12 + -3x

Combine like terms: 12 + -12 = 0
0 + 3y = -12 + -3x
3y = -12 + -3x

Divide each side by '3'.
y = -4 + -1x

Simplifying
y = -4 + -1x

See similar equations:

| (25/36)^(-2/3) | | 0.8d=100 | | 414=18.0 | | d*0.8=100 | | u/9=7 | | 6(x-2)=2(-3+3x) | | 4(x+1.82)=3x | | a=wI | | -4x+8=4x-16-8 | | x^4-22x^2+120=0 | | 136.649+16.4+73.18+2.4878= | | 14+86=15 | | z+149.3=73.5633-1.317 | | x+86=15 | | c=8d+30 | | 22+16+19+15+13= | | 73.9+105+108.0359+197.89= | | -4(x+3)=-12-4x | | 10x-10=6x+6 | | 109.598+197-29.7156-32.87= | | 1.25(m-2)=1.50(m-3) | | -8(x-4)=4(8-2x) | | y=0.5x^2-x^3+1 | | 0.6x+11.6=x-1.04 | | -3(x+5)=-60+6x | | 2(3.14)9(9)+2(3.14)9(27)= | | -0.9x+7.87=-0.7x+2.67 | | 6=2(x+7) | | 32x-6+5x=-23 | | -0.9x+7.87=0.7x+2.67 | | 6x-7=2x+7 | | 9=6(x-7)-3x |

Equations solver categories